Intravascular Ketamine Increases Theta-Burst but Not High Frequency Tetanus Induced LTP at CA3-CA1 Synapses Within Three Hours and Devoid of an Increase in Spine Density - Widman, Allie J.; Stewart, Amy E.; Erb, Elise M.; Gardner, Elizabeth; McMahon, Lori L. (Frontiers in Synaptic Neuroscience, 2018)
In the past 20 years, ketamine has become a promising treatment for Major Depressive Disorder (MDD) due to its rapid and sustain antidepressant effects in patients. A single ketamine treatment causes improvement in depressive symptoms within hours and can last weeks, long after it is eliminated. Previous studies have demonstrated increased synaptic plasticity at CA3-CA1 synapses in hippocampus 24 hrs post ketamine treatment suggesting increased activity-dependent hippocampal function may underlie the antidepressant effects of ketamine. If true, these changes should also occur within hours of treatment, a time when symptoms are first alleviated in patients. To determine if augmented synaptic plasticity is observed at an earlier time point, we measured theta-burst and high frequency tetanus induced long-term potentiation (LTP) at CA3-CA1 synapses 3 hrs following intravascular (IV) ketamine administration. Additionally, we measured basal hippocampal function and spine density to investigate whether connectivity was increased with ketamine treatment. We report that theta-burst but not high frequency tetanus induced LTP is significantly increased 3 hrs after in vivo ketamine with no changes in basal synaptic function or morphology. Our finding supports increased activity-dependent hippocampal function underlying the antidepressant effects of ketamine as it occurs at a time point that correlates with initial improvements of depressive symptoms in patients.